Influence of Sanitary and Preventive Measures on Apiary Productivity - Tursunova, Kamola; Syromiatnykov, Yurii; Ishniyazova, Shakhista; Otabek, Makhmadiyarov (American Journal of Botany and Bioengineering, 2025)
Sanitary and preventive measures are critical for ensuring the productivity and sustainability of modern beekeeping. The presence of infectious and invasive diseases such as varroatosis and nosematosis significantly reduces colony strength, overwintering success, and honey yields. This study analyzed the effectiveness of veterinary-sanitary practices, including hive disinfection, regular replacement of combs, control of hive microclimate, and the use of environmentally safe biopreparations, in reducing disease incidence and improving colony productivity. Field observations in apiaries of Latvia and Ukraine during 2023–2024 demonstrated that colonies managed under strict sanitary regimes exhibited higher brood viability, increased hygienic behavior, and honey yields exceeding those of control colonies by 15–20%. Preventive disinfection of hives and tools, combined with seasonal comb renewal, decreased visible signs of varroa infestation by 18% and reduced nosematosis incidence by 25% compared to conventional management. The results highlight the practical importance of integrating preventive strategies into routine apiculture. Perspectives for further development include the implementation of automated disinfection systems, the application of biocompatible coatings inside hives, and the broader adoption of probiotic and humic-based preparations to enhance colony immunity. Such measures contribute not only to higher productivity but also to the long-term sustainability of beekeeping in temperate climates.